CEA as a Tumor Marker in Predicting Pelvic and Para-aortic Lymph Node Metastasis in Squamous Cell Carcinoma Cervix - BR, Kiran Kumar; Viswanathan, Bhaskar; Reddy, Swathi (Asian Pacific Journal of Cancer Biology, 2024)
Background: Carcinoma cervix is the major cause of death from gynecological malignancies. Isolated paraaortic lymph node metastasis detected on the initial diagnosis of cervical cancers could be addressed via extended paraaortic lymph node irradiation. Serum Carcinoembryonic antigen (CEA) is useful in detecting early Para aortic lymph node (PALN). Materials and Methods: Fifty patients of histologically proven squamous cell carcinoma of cervix have been recruited into the study. We assessed pelvic and Para aortic lymph node status via CT or MRI scans. Serum CEA ranges had been evaluated in all from stage I to IV before starting the treatment. Results: We observed that high pretreatment CEA values were associated with the pelvic and paraaortic lymph node metastasis 65.2% of the patients with high pretreatment CEA value had PALN metastasis (p=0.002). 47.8% of the patients with high CEA had pelvic lymph nodal metastasis (p=0.077) and 70% of the patients with high pretreatment CEA had both Pelvic and PALN metastasis which was statistically significant (p=0.020). Conclusion: Carcinoembryonic antigen levels should help to prognosticate the Carcinoma Cervix patients and predict the presence of Para-aortic and Pelvic lymph nodes. This may be effective tool for detecting early failures in patients with Carcinoma Cervix